Fluid screens, expanded cinema - Marchessault, Janine; Lord, Susan, 1959- (Digital futures., 2007)
"This book considers the shift from traditional cinema to new frontiers of interactive, performative, and networked media. Using the theories of Marshall McLuhan and Gilles Deleuze as a starting point, renowned scholars explore the way in which digital technology is transforming contemporary visual culture."--Book jacket.